Efektivitas Struktur Organisasi Terhadap Kinerja dan Motivasi Guru: Effectiveness of Organizational Structure on Teacher Performance and Motivation - Wijayanti, Christiana Hany; Widodo, Bambang Sigit (STAI Publisistik Thawalib Jakarta, 2024)
The purpose of this study was to determine how the organizational structure variable impacts the dependent variable of teacher performance and motivation, both individually and collectively at Cita Hati West Campus Christian Elementary School, Surabaya. The study used the correlational method of normality test, linearity, simple correlation, and multiple correlations were used to analyze the data as a research sample. using SPSS 21.0 for Windows. Three findings of this study. First, this study found that organizational structure has a positive and significant effect on teacher performance and motivation. Second, this study found that organizational structure has a positive and significant effect on performance. Third, The results of this study indicate that structure has a positive and significant effect on teacher motivation. Therefore, it can be concluded that organizational structure can affect teacher performance and motivation.